Using theory integration to explain online impulse buying behavior in social commerce - Samah Abdelsalam; Naomie Salim; Rose Alinda Alias; Omayma Husain; Sayeed Haider Salih; Ramayah Thurasamy; Muzaffar Hamzah; Mosab Hamdan; Hafiz Muhammed Faisal Shehzad (IEEE, 2024)
Online Impulse Buying Behavior (IBB) significantly increases and contributes to the total S-commerce revenue. Hence, understanding such behavior is critical for an online business to strengthen competitiveness, enhance revenue, and ensure business sustainability. The majority of the prior research used urge-to-buy (UBI) to examine online IBB instead of the actual IBB. Hence, the studies that differentiate between UBI and IBB are limited. Moreover, these studies have concentrated on the impact of consumer characteristics, website, and marketing factors, but they neglected the role of social factors. This study integrated Social Influence and Uses and Gratifications Theories to explore the social factors affecting online IBB. The findings indicate that social influences, entertainment, purposive value, and maintaining interpersonal connectivity influence IBB significantly. UBI also mediates the relationships between social influences and IBB. Impulsiveness moderates the indirect relationships between compliance, internalization, and IBB through UBI. This study has practical implications for social commerce designers, marketers, and managers.